2014
DOI: 10.7314/apjcp.2014.15.21.9347
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Associations between ERCC2 Lys751Gln/Asp312Asn Polymorphisms and Risk of Non-Hodgkin Lymphoma

Abstract: Background: Excision repair crossing-complementing group 2 (ERCC2), also called xeroderma pigmentosum complementary group D (XPD), plays a crucial role in the nucleotide excision repair (NER) pathway. Previous epidemiological studies have reported associations between ERCC2 polymorphisms and non-Hodgkin lymphoma (NHL) risk, but the results have remained controversial. Materials and Methods: We conducted this metaanalysis based on eligible case-control studies to investigate the role of two ERCC2 polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Meanwhile, El-Din et al found no significant association between rs1799793 SNP and DLBCL susceptibility in an Egyptian population, despite A allele carriers having a higher trend for DLBCL [ 27 ]. Inversely, a recent meta-analysis study showed that rs1799793 was negatively correlated with DLBCL risk under Asn (A) vs. Asp (G) genetic model [ 28 ]. These differences might be caused by differences in ethnicity or regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, El-Din et al found no significant association between rs1799793 SNP and DLBCL susceptibility in an Egyptian population, despite A allele carriers having a higher trend for DLBCL [ 27 ]. Inversely, a recent meta-analysis study showed that rs1799793 was negatively correlated with DLBCL risk under Asn (A) vs. Asp (G) genetic model [ 28 ]. These differences might be caused by differences in ethnicity or regions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no significant association has been discovered between rs13181 genotypes and DLBCL risk; while an approximately 1.820 times elevated DLBCL risk was associated with rs13181 C allele. El-Din et al indicated that rs13181 CC genotype carriers had higher susceptibility for DLBCL, but the association was not significant [ 28 ]. However, Worrillow et al demonstrated that rs13181 CC genotype was significantly associated with reduced risk for DLBCL in an English population [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation